Evaluasi Program Keluarga Harapan di Kabupaten Gresik - Thoyib Hadirianto; Sri Wibawani (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to describe the evaluation of the family hope program in Gresik Regency. Based on Gresik Regency which has been named the best hopeful family program management in Indonesia in 2019, but in reality there are still various problems in the distribution of the hopeful family program in Gresik Regency. With descriptive qualitative methods and data collection techniques, namely interviews, observation and documentation, the types of data used are primary data and secondary data. Informants selected as information objects were Gresik District Social Service employees and beneficiary families in Gresik District. The theory used is the theory of policy evaluation according to Dunn (2003), which consists of 6 indicators namely effectiveness, efficiency, adequacy, equity, responsiveness, and appropriatness. The results showed that the evaluation of the implementation of the family hope program in Gresik Regency still did not meet the indicators of effectiveness, equity, adequacy and appropriatness. While the indicators of efficiency and responsiveness are good enough. So that the evaluation of the family hope program policy in Gresik Regency can be assessed as still not optimal.